The effects of habitat structure on red deer (Cervus elaphus) body mass - Jerina, Klemen (Zbornik gozdarstva in lesarstva, 2007)
In most mammalian species, body mass is one of the key factors affecting an individual's fitness. It is therefore important to know the causes of its variability. The present paper analyses the influences of habitat structure and other environmental factors on body mass in red deer. The research is based on data sets concerning 3,920 culled red deer from the entire Slovenia, which are geo-referenced within a kilometer spatial accuracy, and on 28 spatially explicit raster layers of population density, habitat structure variables (e.g. topography, land use, forest structure, roads) and other environmental variables (e.g. air temperature, precipitation, supplementary feeding). After controlling for sex and age of the individual and its date of culling, body weight significantly differs between population areas, most likely as a result of genotype differences and genotype impact on the phenotype, and is also negatively dependent upon population density and the percentage of conifers and positively dependent upon annual mean air temperature and forest/meadow edge density. The stated environmental factors probably influence the achieved energy balance and, therefore, the body mass of red deer by conditioning the quantity and quality of food and energy expenditure of deer.
Keywords: habitat; jelenjad; Slovenia; Slovenija; telesna teža; vpliv okolja